# 2x + 1 = 3x - 2how to solve equation above

*print*Print*list*Cite

### 8 Answers

You need to put all terms containing x to the left side and the rest of the numbers to the right side.

To put the terms containing x to the left you should subtract 3x both sides:

2x - 3x + 1 = -2

To put the terms without x to the right side you should subtract 1 both sides:

-x = -2 - 1

-x = -3

Multiply by -1 both sides:

x = 3

**The solution to the equation above is x = 3.**

2x + 1 = 3x - 2

Move the variables on one side

3x-2x=1+3

x=3

2x + 1 = 3x - 2

1=x-2 subtract 2x from both sides

3=x add 2 to both sides

2x + 1 = 3x - 2

To solve this equation you will have to move the " x " on one side. So subtract 2x on both sides

By subtracting, you should get

**1 = x - 2 **now add 2 on both side in order to get " x " alone

By adding 2 on both sides you should get

**3 = x **which is your answer

2x+1=3x-2

2x+1+2=3x-2+2

2x+3=3x

2x+3-2x=3x-2x

3=1x

3/1=1x/1

x=3

## 2x + 1 = 3x - 2

Answer:

3x - 2x = 1 + 2

x = 3

2x +1 = 3x -2

taking all the x terms in one side and constants in another sides..

2x -3x = -2 -1

-x = -3

cancelling ( -) on both sides, we get

x = 3

First of all bring the x containing terms on left side of the equation and numbers to the right side.

2x+1=3x-2

0r,2x-3x=-2-1

Then solve it

or, -x=-3

Cancel the - sign on both

therefore

x=3